THE INFLUENCE OF PROBLEM-BASED LEARNING ON SCIENCE LITERACY ABILITY OF PHYSICS STUDENTS - Wahyu Istiqomah; Andik Purwanto; Rosane Medriati (Jurnal Pendidikan Matematika dan IPA)
This study aims to determine the effect of problem-based learning on the ability of physics science literacy at SMAN 4 Bengkulu City. The research was conducted in class XI IPA 2. The method used was a pre-experiment with a one group pretest-posttest design. The first stage is the assessment of the test in the form of a pretest (initial test) after which it is given the learning treatment using the problem-based learning model. The last step is given a final test in the form of a posttest. There is an influence on the results of hypothesis testing and the results of students' scientific literacy ability tests before being given treatment and after being given treatment. The test results were hypothesized using the help of SPSS software version 25 obtained H_0 was rejected and H_1 was accepted, using the problem based learning learning model on students' scientific literacy skills on the concept of material Elasticity and Hooke's Law seen from the test results which showed an average posttest result of 80.19% higher than the pretest average (48.52%). Based on the results of the hypothesis test, there is an effect of problem-based learning on the scientific literacy abilities of physics students at SMAN 4 Bengkulu City.